FACTORS AFFECTING FINANCIAL PERFORMANCE IN BANKING COMPANIES - Fatma, Sumaya; Safitri, Teti Anggita (Universitas Muhammadiyah Yogyakarta, 2021)
The financial services authority stated that the industrial profit in the national banking industry, namely in the fourth quarter of 2015 decreased compared to the fourth period of 2014. This can be seen from the indicator of Return On Assets (ROA) of the banking industry which was lower than 2014. In December In 2014 the Return On Assets (ROA) of the banking industry was 2.85%, while in November 2015 the Return On Assets (ROA) was at 2.30%. The purpose of this study was to determine the effect of firm size, leverage and capital structure on the company's financial performance either partially or simultaneously. Firm size uses company assets, leverage is measured using the Debt to Total Asset Ratio (DAR) ratio, capital structure is measured using the Debt to Equity Ratio (DER) ratio and the company's financial performance is measured using return on assets (ROA). The sample used in this study is the sub-sector of companies listed on the Indonesia Stock Exchange for the 2015-2019 period, which amounted to 27 companies. Sampling in this study using purposive sampling technique. The analytical method used in this study is the Multiple Linear Regression analysis method. The results of this study indicate that partially firm size and capital structure have a significant effect on the company's financial performance and leverage has no significant effect on the company's financial performance. Simultaneous research results show that firm size, leverage and capital structure together have a significant effect on the company's financial performance.